DIVIDEND POLICY, TRADING VOLUME AND ORDER IMBALANCE, AND ITS IMPACT ON STOCK PRICE VOLATILITY - Putri Elgi Ramadhani; Erida Herlina (Research in Management and Accounting)
Stock price volatility is a statistical measurement of fluctuations over a certain period. Investors observe stock price volatility to estimate the risk or profit to be gained. High and low stock price volatility depends on information about stock prices. This study aims to determine the effect of dividend yield, dividend payout ratio, trading volume and order imbalance on stock price volatility. The population in this study are companies that are members of the LQ45 index listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The sample was selected using a purposive sampling technique, and 39 companies were selected as samples. The data analysis technique used is multiple linear regression with SPSS 23 software. The results showed that dividend yield, dividend payout ratio and trading volume affect stock price volatility, but order imbalance does not affect stock price volatility.